Self-administration of intranasal influenza vaccine: Immunogenicity and volunteer acceptance. Issue 32 (31st July 2015) - Burgess, Timothy H.; Murray, Clinton K.; Bavaro, Mary F.; Landrum, Michael L.; O'Bryan, Thomas A.; Rosas, Jessica G.; Cammarata, Stephanie M.; Martin, Nicholas J.; Ewing, Daniel; Raviprakash, Kanakatte; Mor, Deepika; Zell, Elizabeth R.; et al.
Abstract Background In outbreak settings, mass vaccination strategies could maximize health protection of military personnel. Self-administration of live attenuated influenza vaccine (LAIV) may be a means to vaccinate large numbers of people and achieve deployment readiness while sparing the use of human resources. Methods A phase IV, open-label, randomized controlled trial evaluating the immunogenicity and acceptance of self-administered (SA) LAIV was conducted from 2012 to 2014. SA subjects were randomized to either individual self-administration or self-administration in a group setting. Control randomized subjects received healthcare worker-administered (HCWA) LAIV. Anti-hemagglutinin (HAI) antibody concentrations were measured pre- and post-vaccination. The primary endpoint was immunogenicity non-inferiority between SA and HCWA groups. Subjects were surveyed on preferred administration method. Results A total of 1077 subjects consented and were randomized (529 SA, 548 HCWA). Subject characteristics were very similar between groups, though SA subjects were younger, more likely to be white and on active duty. The per-protocol analysis included 1024 subjects (501 SA, 523 HCWA). Post-vaccination geometric mean titers by vaccine strain and by study group (HCWA vs. SA) were: A/H1N1 (45.8 vs. 48.7, respectively; p = 0.43), A/H3N2 (45.5 vs. 46.4; p = 0.80), B/Yamagata (17.2 vs. 17.8; p = 0.55). Seroresponses to A components were high (∼67%), while seroresponses to B components were lower (∼25%). Seroresponse did not differ by administration method. Baseline preference for administration method was similar between groups, with the majority in each group expressing no preference. At follow-up, the majority (64%) of SA subjects preferred SA vaccine. Conclusions LAIV immunogenicity was similar for HCWA and SA vaccines. SA was well-tolerated and preferred to HCWA among those who performed SA.